PERAN KONSELOR DALAM PASAR KERJA DI PROVINSI SULAWESI BARAT - Supri Anto Baen; Lilis Lilis; Happy Karlina Marjo (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2024)
In West Sulawesi, young people face difficulties in finding employment because of employment opportunities are limited. By looking at the portrait of the labor market in West Sulawesi Province, counselors can help them through career counseling by working together with various institutions, such as schools, vocational training centers (BLK), even schools. with various institutions, such as schools, vocational training centers (BLK), and even the West Sulawesi Provincial Regional Government of West Sulawesi Province. The approach in this research approach in this research is descriptive qualitative with the data source of labor market portrait in West Sulawesi Province in 2022. West Sulawesi Province in 2022. The purpose of this research is to explain what can be done by counselors in the labor market in West Sulawesi Province. The result of this research The results of this study describe 1) a portrait of the labor market in West Sulawesi Province in 2022 which presents statistical data that includes statistical data on the labor market in West Sulawesi Province. 2022 which presents statistical data that includes information on job seekers, job vacancies, to the salary offered; 2) Counselors can use portrait of the job market in West Sulawesi Province as occupational knowledge in career counseling.